2014
DOI: 10.5812/ircmj.13954
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role of Endogenous Ovarian Hormones Against Learning and Memory Impairments and Brain Tissues Oxidative Damage Induced by Lipopolysaccharide

Abstract: Background:The contribution of neuroinflammation in Alzheimer’s disease (AD) has been widely reported. The effects of female gonadal hormones in both neuroinflammation and brain cognitive functions have also been well considered.Objectives:In the present study, the possible protective role for endogenous ovarian hormones against learning and memory impairment as well as brain tissues oxidative damage induced by lipopolysachride (LPS) was investigated in rats.Materials and Methods:The rats were divided into fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 67 publications
3
26
0
Order By: Relevance
“…Using animal models, it has been indicated that administration of cytokines or other immune system stimuli including LPS deteriorate hippocampus-dependent learning and memory process 24 . Recently, the brain tissues oxidative damage was considered to have an important role in deleterious effects of LPS on learning and memory 16 . The cerebral cortex and hippocampus which play crucial roles in learning and cognition have been shown to be very sensitive to the oxidative stress 28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using animal models, it has been indicated that administration of cytokines or other immune system stimuli including LPS deteriorate hippocampus-dependent learning and memory process 24 . Recently, the brain tissues oxidative damage was considered to have an important role in deleterious effects of LPS on learning and memory 16 . The cerebral cortex and hippocampus which play crucial roles in learning and cognition have been shown to be very sensitive to the oxidative stress 28 .…”
Section: Discussionmentioning
confidence: 99%
“…When the animals were entered completely into the dark compartment, the door was closed and an electrical shock (2 mA, 2 s) was delivered to the floor of the compartment. At 3, 24, 48 and 72 h later, the animals were again located in the light compartment for 15 s, after opening the guillotine door they gave access to the dark compartment within a period of 300 s. Then the time latency to enter into the dark room as well as the time spent by the animals in the light and dark compartments were recorded and defined as retention trail 16,17 .…”
Section: Passive Avoidance (Pa) Testmentioning
confidence: 99%
“…The rat's estrous cycle is including proestrous, estrous, metaestrous and diestrous 9 . In proestrous phase, the estrogen levels are in high level.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, the rats were held in a non-stress position and quickly lavaged with approximately 1ml saline. Slides were read using light microscopy, and estrous categories were classified based on cytological characteristics 9 .…”
Section: Vaginal Cytologymentioning
confidence: 99%
“…The absorbance of DTNB reagent was also read as the blank (B). Total thiol concentration (mM) was calculated using the following equation (37)(38)(39)(40):…”
Section: Biochemical Assessmentmentioning
confidence: 99%